A CORRELATIONAL STUDY BETWEEN THE MASTERY OF PAST TENSE AND THE ABILITY OF WRITING RICOUNT TEXT - Ni Wayan Sri Ayu Purnami; I Nengah Astawa; I Komang Budiarta (Academic Journal on English Studies (AJOES), 2021)
This research was intended to know if there was any positive corralation between themastery of past tense and the ability of writing recount text of the twelfth grade students ofSMAN 1 Gianyar in academic year 2020-2021. There were in all 75 students taken as thesamples of the research using random sampling with lotery system. In the researchinstruments the samples were asked to write sentences in recount text and textconstruction test. The data obtained were statistically analysed using presequisit analysis(normality and homogeneity test) and Person Product moment correlational and t-test. It isrevealed that the alternative hypothesis is vividly accepted. It means that there wassignificant correlation between the mastery of past tense and the ability of writing recounttext of the twelfth grade students of SMAN 1 Ganyar in 2020-2021 academic year.